Digital marketing communications and its impact on the potential and current clients of Ogilvy & Mather - Ahamed, Md. Mahedi (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.